Suicide commandoes - Poe, Fernando, Jr; Vasquez, Romeo; Estrada, Joseph; Laxa, Espiridion
Their task is to destroy the airport and bring Lt. Raul Toledo (Romeo Vasquez) safe to a certain destination. The Suicide Commandoes have to risk everything to fulfill this mission and compliment each other. The struggle is really tough and nobody knows what the future holds, and nobody could question their conviction.